Cognitive Impairment and Risk of All‐Cause and Cardiovascular Disease Mortality Over 20‐Year Follow‐up: Results From the BLSA. Issue 15 (7th August 2018) - An, Ji; Li, Haibin; Tang, Zhe; Zheng, Deqiang; Guo, Jin; Liu, Yue; Feng, Wei; Li, Xia; Wang, Anxin; Liu, Xiangtong; Tao, Lixin; Hou, Chengbei; et al.
Abstract : Background: Cognitive impairment may increase the risk of all‐cause and cardiovascular disease (CVD) mortality. This study examined the association between cognitive function and risk of all‐cause and CVD mortality among the elderly in Beijing, China. Methods and Results: A total of 1996 participants aged ≥55 years at baseline were enrolled from the BLSA (Beijing Longitudinal Study of Aging). Cognitive function was assessed using the Mini‐Mental State Examination (MMSE), and participants were categorized as: <18, 18 to 23, 24 to 27, and 28 to 30. Cox proportional hazard models were used to estimate the association. Hazard ratio (HR) and 95% confidence interval (CI) were reported. During a 20‐year follow‐up, 1122 (56.21%) participants died, 478 (42.60%) of whom died of CVD. Compared with MMSE scores of 28 to 30, participants with MMSE scores of <18 were independently associated with all‐cause mortality (hazard ratio, 2.14; 95% confidence interval, 1.59–2.87; P <0.001) and CVD mortality (hazard ratio, 4.52; 95% confidence interval, 2.80–7.30, P <0.001). Each 5‐point decrease in MMSE score was associated with a 34% increased risk of all‐cause mortality and a 56% increased risk of CVD mortality. This relationship remained statistically significant after using the competing risk model to consider non‐CVD death as a competing risk event. Conclusion: Cognitive impairment measured by MMSE score was associated with elevated risk of all‐cause and CVD mortality among the elderly in Beijing, China.